Traumatic Events and Obsessive Compulsive Disorder in Children and Adolescents: Is There a Link? - Lafleur, Daniel L. (2010)
BACKGROUND: The extant literature supports an association between psychological trauma and development of OCD in adults, and this link is a plausible mediator for environment gene interactions leading to phenotypic expression of OCD. OBJECTIVE: To explore the relationship between OCD and traumatic life events in children and adolescents. METHODS: We examined the prevalence of traumatic life events and PTSD in a large sample of systematically assessed children with OCD. OCD symptoms and severity were assessed using the Children’s Yale Brown Obsessive Compulsive Scale (CY-BOCS) in those with and without concurrent PTSD. RESULTS: Rate of PTSD and trauma exposure was higher in children with OCD than in a comparable control group of non-OCD youth matched for age, gender and SES. Children with concurrent PTSD had more intrusive fears and distress and less control over their rituals than children with OCD but without PTSD. Total CY-BOCS scores were higher in those with concurrent PTSD. Specific type of OCD symptoms was not altered by a PTSD diagnosis. CONCLUSIONS: A history of psychologically traumatic events may be over-represented in children with OCD. Given the need to search for non-genetic factors that may lead to onset of OCD, better and more systematic methods to obtain and quantify psychologically traumatic life events are needed in clinical populations.